Pembuatan Media Video Pembelajaran Interaktif Teknik Pemijatan Pada Wajah Di SMK - Kiki Ida Dwijayanti; Suhartiningsih Suhartiningsih (Syntax Idea, 2021)
The purpose of making this article is to provide knowledge that the creation of learning video media in VOCATIONAL in the pandemic era iseffective. This article uses kuantitative research method using questionnaires shared through google form, where questionnaires taken are edated from beauty journals. The results of this study show the existence of advantages and disadvantages that can be corrected. Some of these advantages include high attractiveness, suitability of typefaces, and narratives that support learning videos and interestingly presented materials that have included the entire facial massage material with a percentage of 100% of the overall expert validator and a percentage of 66.7% with the level of likes to state the background, fonts and narrative used to support the clarity of the material. Although there are some improvements in the introduction, this interactive learning video is already good and can be used by a vocational school teacher to help with the student learning process.